2021
DOI: 10.1021/acsomega.1c01167
|View full text |Cite
|
Sign up to set email alerts
|

Galangin and Kaempferol Alleviate the Indomethacin-Caused Cytotoxicity and Barrier Loss in Rat Intestinal Epithelial (IEC-6) Cells Via Mediating JNK/Src Activation

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) like indomethacin and others are widely used in clinics, but they have the potential to cause severe gastrointestinal damage including intestinal barrier dysfunction. Thus, two flavonols galangin and kaempferol with or without heat treatment (100 °C, 30 min) were assessed for their effect on indomethacin-damaged rat intestine epithelial (IEC-6) cells. In total, the cell exposure of 300 μmol/L indomethacin for 24 h caused cell toxicity efficiently, resulting in decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The determination of LDH release according to the method of Fan et al reported. 19 AML-12 and IEC-6 cells were seeded in 96-well plates at 3 × 10 3 cells/well, incubated for 24 h, and adhered. The medium was then discarded after being incubated in serum-free medium for 12 h. Then, the cells in each well were incubated with 100 μL of media containing different concentrations of polyphenols (25, 50, and 100 μmol/L) for 24 h, and then the culture medium was discarded.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of LDH release according to the method of Fan et al reported. 19 AML-12 and IEC-6 cells were seeded in 96-well plates at 3 × 10 3 cells/well, incubated for 24 h, and adhered. The medium was then discarded after being incubated in serum-free medium for 12 h. Then, the cells in each well were incubated with 100 μL of media containing different concentrations of polyphenols (25, 50, and 100 μmol/L) for 24 h, and then the culture medium was discarded.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The determination of LDH release according to the method of Fan et al reported . AML-12 and IEC-6 cells were seeded in 96-well plates at 3 × 10 3 cells/well, incubated for 24 h, and adhered.…”
Section: Methodsmentioning
confidence: 99%
“…The paracellular permeability of the assessed cell monolayer was also measured in the Transwell inserts (12 mm diameter, 0.4 μm pore size, polyester membranes, Corning) using the FD-4 and FS-Na methods [ 29 , 30 ]. When the monolayer was cultured to a TEER value of 50 Ω cm 2 , FD-4 (0.5 mg/mL) or FS-Na (0.08 mg/mL) of 0.5 mL, together with the culture medium of 1.5 mL, was added to the apical and the basolateral sides, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Fan et al reported that pretreatment with galangin alleviated indomethacin‐induced barrier loss in rat intestinal epithelial cells and promoted the expression of three tight junction proteins, zonula occluden‐1, occludin, and claudin‐1. In addition, galangin decreased the intracellular Ca 2+ concentration and the phosphorylation levels of JNK and Src induced by indometol, which suggested galangin reduces intestinal damage caused by indomethacin by inhibiting Ca 2+ ‐mediated JNK/Src activation (Fan et al, 2021). These results suggested that galangin might be a potential therapeutic agent to alleviate NSAIDs induced intestinal injury.…”
Section: Promising Role Of Galangin In Various Diseasesmentioning
confidence: 99%
“…To date, a battery of bioactivities of galangin have been elucidated, involving anti‐inflammation (Song, Kim, et al, 2021), antibacterial effect (Cushnie & Lamb, 2006), anti‐oxidative stress and aging (Lee et al, 2022), anti‐fibrosis (Wang et al, 2020), as well as antihypertensive effect (Chaihongsa et al, 2021). Given these outstanding bioactivities, an increasing number of studies are focusing on the potential of galangin in treating human diseases, such as cancer (Deng et al, 2021), rheumatoid arthritis (Deng et al, 2022), osteoporosis (Li et al, 2021), osteoarthritis (Huh et al, 2013), Gastrointestinal disease (Fan et al, 2021), stroke (Guan et al, 2021), diabetes mellitus (Aloud et al, 2020), neuropathies (Choi, Park, et al, 2017), and others (Figure 1). More importantly, the molecular mechanisms of galangin in regulating the above‐mentioned diseases have been partially illustrated, which greatly facilitates the development of galangin as a drug candidate or dietary supplement.…”
Section: Introductionmentioning
confidence: 99%